An Examination of Organizational Cynicism from a Strategic Management Perspective: Strategic management and organizational cynicism - Cagiran Kendirli, Hulya; Arli, Sadi (Journal of Economic Development, Environment and People, 2026)
Strategic management is a management technique that outlines what an organization does, its reason for existence, and the goals it wants to achieve in the future. When creating strategies to achieve goals in an organization, the first stage involves planning these strategies within the framework of the company's vision, then implementing these planned strategies, and finally, reviewing and monitoring the results of the implementation. Strategic management is a management technique used in making future-oriented decisions in an organization. (Aktan, 2003; Karakaş, 2003; Dinçer, 2003). A person who believes that individuals only look out for their own interests and therefore views everyone around them as self-serving is called a "cynic," and the school of thought that describes cynical individuals is called "cynicism." It is stated that many of the main beliefs associated with cynicism, such as honesty, fairness, and sincerity, are abused for individual gain. The words "skepticism," "doubt," "distrust," "unbelief," "pessimism," and "negativity," which are cited as synonyms for cynicism, also encompass, in a civilized interpretation, the human tendency to "find faults, be hard to please, and be critical" (Erdost, 2007). This study will examine the concept of organizational cynicism from a strategic management perspective and evaluate its positive or negative contributions to the organization.